(3QSGdI aj GdYed HGdBdI GdTcGRjIs
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg QSGdI dWjaI ai GdYed HGdBdI GdeSeGg HGdTcGRjI s
(3BNQgG (B:s
(3Cf JCNP ZGjI GQJaGY GdOQLI hZGjI GdfXjQ eJMaXkG hfUageG aeG cGf agh GdCUd s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs